USE OF 3D-PRINTED MODELS IN MEDICAL EDUCATION - Guimarães, Gabriela Aimée; Cavalcante, Gabriel Cremonez; Arruda, Jalsi Tacon (CIPEEX, 2025)
This study aimed to evaluate the efficiency of using 3D-printed bone parts in Human Anatomy classes in the first semester of the Medicine course at the Evangelical University of Goiás. The parts were produced on a 3D printer and used in an activity to identify the bones and muscles of the left human foot. A questionnaire about the structures studied in class was administered before and after the activity. There were 130 responses to the first questionnaire and 105 responses to the second, with varying rates of correct answers as the difficulty of the questions increased. As a result, it was observed that the success rates in the questionnaires increased substantially after the activity with the 3D pieces, which reinforces the thesis that there is space, application, and usefulness in the production of the pieces in the medical educational context. It was concluded that the bone pieces are efficient in assisting the teaching process of the Human Anatomy discipline.